USE OF ACTIVE METHODOLOGY IN NURSING GRADUATION COURSES (CIPEEX, 2022)
OBJECTIVE: TO DESCRIBE THE APPLICABILITY OF THE ACTIVE METHODOLOGY IN UNDERGRADUATE NURSING COURSES IN ORDER TO OBTAIN THE SKILLS AND COMPETENCES REQUIRED BY THE NURSING PROFESSIONAL IN ACCORDANCE WITH THE NATIONAL CURRICULAR GUIDELINES (DCNS). METHODOLOGY: THIS IS AN INTEGRATIVE REVIEW OF THE LITERATURE COMPOSED OF ARTICLES PUBLISHED IN THE VIRTUAL HEALTH LIBRARY (VHL) AND AVAILABLE IN FULL TEXT IN THE DATABASES: LILACS, MEDLINE AND BDENF, IN THE PERIOD BETWEEN 2010-2016. RESULTS: THE DATA WERE ORGANIZED INTO TABLES, SYNOPTIC TABLES, FIGURES AND LATER CATEGORIZED. FIFTEEN ARTICLES WERE INCLUDED IN THE PRESENT STUDY. THE FOLLOWING CATEGORIES EMERGED: NEW DISCOVERIES AND CHALLENGES OF THE TEACHING-LEARNING PROCESS IN UNDERGRADUATE NURSING COURSES; AND TEACHING-LEARNING STRATEGIES IN UNDERGRADUATE NURSING COURSES. CONCLUSION: THE STUDY EVIDENCED DIFFICULTIES IN RELATION TO THE ACTIVE TEACHING / LEARNING METHODS IN THE TRAINING OF NURSES, EDUCATIONAL INSTITUTIONS AND THE TEACHERS THEMSELVES HAVE TO THINK, AND RETHINK THE CONSTRUCTION OF NEW VIABILITY OF ACTIONS THAT MODIFY THE WAY OF ACTING FOR THE SCOPE SUCCESS IN THE TEACHING-LEARNING PROCESS.
Keywords: Methodology. Active Methodology. Nursing Education. Nursing Education